Media literacy and e-democracy in the EU - Rek, Mateja (Routledge, 2026)
Media Literacy and E-Democracy in the EU examines the crucial role of media literacy in strengthening e-democracy within the European Union (EU).In an era where digital media increasingly shape democratic processes, the EU faces both new opportunities and challenges in promoting active citizenship and transparent governance. This book explores how media education aimed at advancing digital media literacy can serve as the foundation for informed and responsible civic engagement, helping to build a more resilient democratic society. Drawing on a comprehensive analysis of current e-democracy initiatives in the EU, the book offers a fresh perspective on the relevance of media education to advance citizens' digital media literacy. It focuses on the EU due to its unique governance features and distinct digital policy framework. However, its insights and best practices are relevant globally, as media literacy and democratic engagement are universal challenges. The interplay between fast advancements of digitalisation of communication, media literacy and citizens' ability and willingness to participate actively in public affairs is examined in depth.Interdisciplinary in approach, this book will interest students and scholars in political science, media studies, sociology and European studies, as well as policymakers and civil society actors focused on digital governance and civic engagement. Media professionals, journalists and educators will also find it valuable for understanding and shaping democratic participation in the digital age.
Keywords: Democracy -- European Union countries.; Media literacy -- Political aspects -- European Union countries.; Political participation -- Technological innovations -- European Union countries.; elektronické knihy; electronic books